A study of mechanical automation system for applying at Serunding Machine - Mohammad Shobbri, Hazman; Hassan, Suhaimi (2023)
This thesis problem statements about the serunding production until now still doing in half manual and half automatic method or fully manual method and time consumption is taking too long along with the increasing the labor cost and energy. The objective of this research is the development and implementation of a mechanical automated system for applying serunding, a traditional Malaysian meat floss, at a serunding machine. by using Programmable Logic Controller (PLC) and to study the simulation process of serunding production. Moreover, the scope of study is using a PLC system including timer and counter. Additionally, using software automation studio and CX programmer to make the automation system input and output data. The significance of study in this project is about Development of Mechanical Automation System for Serunding Machine is hoped to get make the Serunding Machine can run smoothly using PLC and to get less production time, production cost and labor cost when making the Serunding